"La vie en rose": A positive shift of autobiographical memory in Alzheimer's Disease. (January 2020) - El Haj, Mohamad; Boudoukha, Abdelhalim; Moustafa, Ahmed A.; Antoine, Pascal; Allain, Philippe; Gallouj, Karim
Highlights: We evaluated emotion regulation of autobiographical memory in Alzheimer's disease. AD patients tend to attribute positive meaning to positive memories. They also tend to view negative memories from a less negative perspective. AD patients may positively re-interpret negative memories. Abstract: We investigated emotional regulation of autobiographical memories in Alzheimer's disease (AD). AD patients and control participants were asked to retrieve memories in response to "happy" and "sad" cues. Participants were also asked to rate the emotional valence of memories at retrieval as well as at the moment the events were encoded. Results showed that both control participants and AD patients rated memories cued by "happy" as more positive when retrieved than when encoded. Both control participants and AD patients also rated memories cued by "sad" as less negative when retrieved than when encoded. Furthermore, emotional regulation (i.e., emotional variation across retrieval and encoding of memories) was significantly correlated with depression in AD patients and control participants. These findings suggest a cognitive reappraisal strategy by which AD patients 1) attribute positive meaning to positive memories, and 2) view negative emotional memories from a less negative perspective, demonstrating an ability to re-interpret the meaning of these memories, and thereby, to change their emotional impact. This reappraisal strategy seems to be related with depression as depressive symptoms was inversely correlated with cognitive reappraisal in AD.